THE PHENOTYPIC PERFORMANCE OF KAMBRO CROSSBREEDS OF FEMALE BROILER COBB 500 AND MALE PELUNG BLIRIK HITAM - Mahardhika, I Wayan Swarautama; Daryono, Budi Setiadi (Buletin Veteriner Udayana; Vol. 11 No. 2 Agustus 2019DO - 10.24843/bulvet.2019.v11.i02.p12, 2019)
This research was conducted to measure the phenotypic performance of Kambro crossbreeds of Pelung Blirik Hitam and Broiler Cobb 500. Based on Body Weight (BT) measurement, Kambro population (n = 17) has an average BT of 1,244.14 ± 453.82 grams significant (p <0.01) to F 1 Pelung (n = 7) with an average BT of 602.88 ± 79.93 grams in 8 weeks period with ad libitum diet of standard feed. Phenotypic performance of Kambro significant to F 1 Pelung based on the measurement of linear bodyweight parameter, vitality parameter, PPa-PBe parameter and phenotype parameter. Kambro has the phenotype combination of parental generation based on phenotype parameter. PPa parameter was suitable BT estimation model based on non-linear quadratic regression (r = 0.956) with formula 1.84E3 ±3.54E2*x+31.73*x 2 . Difference between chicken group (p<0.014) was significant to BT and interaction between group and linear bodyweight parameter was not significant based on Analysis of Covariance. The mortality rate of Kambro was lower than F 1 Pelung with the absent of vaccination in semi-intensive rearing system. As the size of hybrids population was limited, research findings must be validated with larger population size of hybrids.